PENGARUH FITUR CASHBACK DAN DISCOUNT DOMPET DIGITAL (E-WALLET) TERHADAP PENGAMBILAN KEPUTUSAN KEUANGAN GENERASI Z MELALUI KONSTRUK TECHNOLOGY ACCEPTANCE MODEL (TAM) DI UNIVERSITAS MUHAMMADIYAH MAKASSAR - Miranda; Syamsuddin; Muhaimin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of cashback and discount features of digital wallets (e-wallet) on Generation Z financial decision-making through the Technology Acceptance Model (TAM) approach. This study employed a quantitative associative method using path analysis (path analysis) with SPSS software. Data were collected from 111 respondents who were active students at Universitas Muhammadiyah Makassar, Generation Z aged 18–30 years, and active users of digital wallets who had transacted using cashback or discount features at least once. The results showed that cashback had a positive and significant effect on perceived usefulness (β=0.432, sig.=0.000) and perceived ease of use (β=0.382, sig.=0.000). Discount also had a positive and significant effect on perceived usefulness (β=0.239, sig.=0.005) and perceived ease of use (β=0.382, sig.=0.000). Perceived usefulness and perceived ease of use significantly influenced attitude toward using (β=0.401 and β=0.340, sig.=0.000). Attitude toward using significantly influenced behavioral intention to use (β=0.570, sig.=0.000), and behavioral intention to use significantly influenced financial decision-making (β=0.502, sig.=0.000). The overall coefficient of determination (R²) of the full model reached 0.99, indicating that the model explains 99% of variance in financial decision-making. The Sobel test confirmed that all mediating paths were significant. The findings indicate that cashback is more dominant than discount in influencing Generation Z e-wallet usage behavior and financial decision-making.